“Los efectos jurídicos asociados a la retención indebida del menor y sus consecuencias al desarrollo integral y convivencia familiar” - Luisa Johanna, Padilla Cruz (2020)
The improper withholding of the child or adolescent is established in Article 125 of the Organic Code for Children and Adolescents. It determines that the parent who wrongly retains his child will have a penalty, compensation, and reparation to the father affected by the retention and may even issue a personal urgency against him or her. It is apparent such precision made by the regulations. However, we are in a dilemma by neglecting the damage or affectation that improper withholding can cause in the child. The consequences range might vary from psychological, educational, legal, emotional, and affective consequences in the child, girls, or teenager. Given this statement, the Organic Code for Children and Adolescents neglects and lacks a type of compensation or recovery of the improperly retained child. On the other hand, two substantial rights of children and adolescents are undermined, the right to their integral development, and the right to family life, rights mainly affected by disagreements among their parents. This research project intends to carry out a legal and doctrinal analysis of both the legal figures of the tenure and visitation regime and the child's improper withholding and determine the effects that such retention causes to the child, mainly their development rights integral and family life. Keywords: tenure, visitation, improper withholding, integral development, family life.